Identification of Mechanical Properties of Fiber-Reinforced Composites - R.A. Kayumov; S.A. Lukankin; V.N. Paimushin; S.A. Kholmogorov (Учёные записки Казанского университета: Серия Физико-математические науки)
Techniques are developed for identification of the mechanical properties of fiber-reinforced composites according to the results of tests on tension, compression, and bending. The case of nonlinear elastic material is considered. To approximate the tension-to-bending ratios, a multimodule dependency of stress on deformations is accepted. The parameters of this dependency are determined by tests on tension and bending. The transverse-bending modulus is calculated by solving inverse bending problems according to the results of tests with long and short samples. These techniques are applied to analysis of the experimental data obtained for HSE 180 REM carbon fiber tape with straight fibers and EDT-69NM epoxy binder.